Earthquake Focal Mechanisms and Stress Field for the Intermediate‐Depth Cauca Cluster, Colombia. Issue 1 (25th January 2019) - Chang, Y.; Warren, L. M.; Zhu, L.; Prieto, G. A.
Abstract: Beneath southwestern Colombia, intermediate‐depth earthquakes in the Cauca cluster locate in the subducting Nazca plate and in two columns extending ~40‐km into the mantle wedge above the slab. To investigate the cluster, we determine focal mechanisms for 69 small‐to‐moderate‐sized (2.3 ≤ Ml ≤ 4.7) earthquakes in the cluster by fitting short‐period body wave waveforms using the cut‐and‐paste method. The focal mechanisms have various faulting types and variably oriented nodal planes. We invert the focal mechanisms of the intraslab earthquakes for the intraslab stress field but cannot fit the region with a homogeneous stress tensor. We find that the principal stress axes rotate with the slab geometry, which has a concave shape and increases in dip angle from north to south. The northern region has slab normal compression and similar‐magnitude maximum and intermediate principal stresses. The minimum stress axis is oriented ~41° counterclockwise from the downdip direction. In the steeper southern region, the intermediate stress axis orients in the downdip direction. Deviation from a typical downdip extensional stress field may result from a buoyant young slab, an eastward mantle flow push, and/or along‐strike compression from the concave shape of the slab. This stress field would allow slip along preexisting faults of various orientations, such as the trench‐perpendicular seafloor features presently observed offshore, and contribute to the apparent heterogeneity of the intraslab stress field. The mantle wedge earthquakes also have various focal mechanisms but tend to have a subvertical nodal plane that aligns with the earthquake locations. Key Points: Cauca cluster earthquakes have various focal mechanisms with variably oriented nodal planes inconsistent with a homogeneous stress tensor The average intraslab stress field has slab normal compression with in‐slab extension oriented ~45° from the downdip direction Deviation from a typical downdip extensional stress field may result from a young slab, mantle flow push, or a concave shape of the slab